Investigation In Two Wheels Mobile Robot Movement: Stability and Motion Paths - Abdulrahman A.A. Emhemed (IAES International Journal of Robotics and Automation (IJRA), 2013)
This paper deals with the problem of dynamic modelling of inspection robot two wheels. Fuzzy controller based on robotics techniques for optimize of an inspection stability. The target is to enhancement of robot direction and avoids the obstacles. To find collision free area, distance-sensors such as ultra-sonic sensors and laser scanners or vision systems are usually employed. The distance-sensors offer only distance information between mobile robots and obstacles. Also the target are shown can be reached by different directions. The fuzzy logic controller is effect to avoid the abstacles and get ideal direction to “the target box”.